Waist circumference is associated with major adverse cardiovascular events in male but not female patients with type-2 diabetes mellitus - Xing, Zhenhua (Cardiovasc Diabetol, 2020)
BACKGROUND: Although studies have shown that waist circumference (WC) is positively associated with an increased risk of cardiovascular diseases among the normal population, few studies have investigated WC in patients with type-2 diabetes mellitus (T2DM). METHODS: This was a post hoc analysis of the Action to Control Cardiovascular Risk in Diabetes (ACCORD) study. The Cox proportional hazards models was used to investigate the relationship between WC and major adverse cardiovascular events (MACEs) in T2DM patients with cardiovascular disease (CVD) or high risk factors of CVD. RESULTS: A total of 10,251 T2DM patients (6299 men [61.4%], 3952 women [38.6%]) were included in our analysis. The mean age was 64.0 ± 7.53 years. After a mean follow-up at 9.2 ± 2.4 years later, 1804 patients (event rate of 23 per 1000 person-years) had developed MACEs. MACEs rates in men and women were 18.0 and 26.0 events per 1000 person-years, respectively. After multivariable adjustment, each increase in WC of 1 SD increased the risk of MACEs (HR: 1.10, 95% CI 1.04–1.17; P < 0.01) in men, with a non-significant increase in MACEs (HR: 1.04, 95% CI 0.95–1.13; P = 0.40) in women. Compared with those in the first quartile of WC, male patients in the fourth quartile of WC had a hazard ratio (HR) of 1.24 (95% CI 1.05–1.46) for MACEs; female patients in the fourth quartile of WC had an HR of 1.22 (95% CI 0.96–1.56) for MACEs. CONCLUSIONS: Higher WC is associated with increased risks of MACEs in male but not female T2DM patients. Trial registration URL: http://www.clinicaltrials.gov. Unique identifier: NCT00000620)